Water Level Monitoring for Flood Early Mitigation Based on Internet of Things (IoT) - Nur Syamsi; Maria Ulfah; Dwi Lesmideyarti (Politeknik Pertanian Negeri Samarinda, 2024)
Flooding is a disaster that often threatens communities, especially in high-risk areas. It is not surprising that this disaster causes many losses to the community morally and materially. This is because the area is on the riverbank and is the lowest point. The purpose of this final project is to design a flood early warning system as a water level monitoring to minimize the losses caused by floods with a water level monitoring tool to provide early warning to the community in the event of a flood. This water level monitoring tool utilizes solar panels as an energy source, where this tool uses ultrasonic sensors as water level detection and rain sensors as rainfall detection. This tool requires 28.6 Watts of power to power the system and the accuracy of the ultrasonic sensor is 99.94% with an average ultrasonic sensor error of 0.05%. This water level monitoring tool will help improve the flood early warning system, thus enabling the community to take appropriate mitigation steps before floods reach dangerous levels. Thus, losses due to flooding can be reduced, and assets can be restored, communities can be better protected from the threat of flooding.